Iodine deficiency in Russia: Current state of the problem, global practice and new approaches to therapy - I. A. Barkovskaya; A. G. Kruchinin; I. V. Rozhkova (Пищевые системы)
Iodine performs a number of important functions in the body, participating in the synthesis of thyroid hormones, which creates the need for constant replenishment of the element in adequate amounts. Continuous monitoring of micronutrient deficiency in the Russian Federation reveals low average daily iodine intake and an increase in the number of cases of thyroid diseases in the period from 2010 to 2020. This actualizes the need to develop new therapeutic and preventive approaches to replenish iodine deficiency. The aim of the review is to analyze the problem of iodine deficiency in Russia and existing practices of its leveling in order to develop a new approach to the prevention and treatment of iodine deficiency conditions. The sample includes publications in Russian and English in the period from 2002 to 2023, using the resources of scientific metric databases Elibrary, Google Scholar, CyberLeninka, PubMed and ScienceDirect. The research work showed that the common practice of eliminating iodine deficiency is to increase the level of consumption of the trace element in the diet, the consequence of which is the availability of a wide range of iodized food supplements and products on the market. However, the analysis of the current functional nutrition sector has revealed a number of drawbacks associated with low bioavailability of the element and its resistance to technological factors in the production of food products. The article presents the key factors influencing the effectiveness of nutritional supplements being developed for nutritional correction of iodine deficiency. They are based on the evaluation of existing means of prevention. The study proposes the development of the technology of whey hydrolysates enriched with iodine and zinc. Application in food production of a food additive based on protein components of milk whey opens new opportunities for processing of secondary dairy raw materials and for full utilization of all milk components. The rich amino acid composition of the additive helps to increase the concentration of essential trace elements in products, as amino acid residues are able to bind iodine and chelate zinc.